Modulation of Correlated Segment Fluctuations in IDPs upon Complex Formation as an Allosteric Regulatory Mechanism. Issue 16 (3rd August 2018) - Beier, Andreas; Schwarz, Thomas C.; Kurzbach, Dennis; Platzer, Gerald; Tribuzio, Francesca; Konrat, Robert
Abstract: Molecular recognition of and by intrinsically disordered proteins (IDPs) is an intriguing and still largely elusive phenomenon. Typically, protein recognition involving IDPs requires either folding upon binding or, alternatively, the formation of "fuzzy complexes." Here we show via correlation analyses of paramagnetic relaxation enhancement data unprecedented and striking alterations of the concerted fluctuations within the conformational ensemble of IDPs upon ligand binding. We study the binding of α-synuclein to calmodulin, a ubiquitous calcium-binding protein, and the binding of the extracellular matrix IDP osteopontin to heparin, a mimic of the extracellular matrix ligand hyaluronic acid. In both cases, binding leads to reduction of correlated long-range motions in these two IDPs and thus indicates a loosening of structural compaction upon binding. Most importantly, however, the simultaneous presence of correlated and anti-correlated fluctuations in IDPs suggests the prevalence of "energetic frustration" and provides an explanation for the puzzling observation of disordered allostery in IDPs. Graphical abstract: Unlabelled Image Highlights: Correlation analysis of PRE NMR data reveals correlated segment fluctuations in IDPs. NMR demonstration of energetic frustration in IDPs and its relevance for binding Release of structural constraints in IDPs upon protein binding Heparin binding of osteopontin facilitates conformational sampling and binding. Calmodulin binding of α-synuclein releases compaction and impacts fibril formation.